Comparison of electron density measurements from CSES and Swarm satellites with GNSS ionospheric tomography data. Issue 6 (15th March 2023) - Chen, Biyan; Cao, Hengrui; Wang, Jinyong; Huang, Jianping; Miao, Zelang
Abstract: Electron density measurements obtained from China Seismo‐Electromagnetic Satellite (CSES) and Swarm-B can play an increasingly important role in the study of ionosphere above F2 peak height. This study presented a comprehensive comparison of electron density products obtained from Langmuir probe mounted on CSES and Swarm-B with ionospheric tomography for a whole year period of 2019. CSES was fully compared with Swarm-B on a global scale, including both absolute and relative differences, and a new index called NFI was developed to better quantify the similarity between two latitudinal profiles of electron density. CSES and Swarm-B were then compared with tomography respectively in four regions, roughly located in America, Europe, Australia and China. Results indicated that CSES data are consistent with Swarm-B, as NFI values exceed 0.6 for most of the analyses. Tomography and Swarm-B were found to have a good agreement as their biases are less than 0.2 × 10 5 el/cm 3 in general. For the comparison between CSES and tomography, the bias increased to around 0.6 × 10 5 el/cm 3 but the standard deviation changed slightly, validating the underestimation of electron density by CSES. The spatiotemporal comparisons of CSES and Swarm-B with tomography showed that: 1) the differences in electron density were relatively low in middle latitudes and increased rapidly in the regions of equatorial ionization anomaly; 2) Swarm-B has a better consistent with tomography than CSES, but both are capable of detecting ionosphere anomalies such as midlatitude arcs; and 3) CSES and Swarm-B both can capture the seasonal changes of electron density, while their values are basically smaller than those from tomography in Spring and Summer months.